Clinical evaluation, accurate diagnosis and treatment of four pedigrees with Fabry's disease - Gou, Peng; Leng, Jie; Cheng, Xinran; Zhang, Jing (Frontiers in Pediatrics, 2023)
Objective This article analyzes the data of four families with mutations of the GLA (galactosidase) gene with a special focus on the clinical presentation, diagnosis, and interdisciplinary clinical management of Fabry disease (FD) and enzyme replacement therapy (ERT) treatment, and has the aim to assess more accurate prevention and treatment strategy. Methods The MSSI (Mainz Severity Score Index) scale was used to evaluate the clinical data of five children diagnosed in our hospital, and the genotypes of all the patients with FD were collected. Two of the male children started ERT. We summarize the clinical effect and the evaluation of globotriaosylsphingosine (Lyso-GL-3) before and after treatment. Results Five children were confirmed as having FD using the family histories, clinical manifestations, α-galactosidase A (a-Gal A) activity, and genetic test results. Two children used agalsidase α every 2 weeks regularly, after ERT. Their clinical symptoms improved, their pain intensity was significantly relieved, and upon re-examination their Lyso-GL-3 decreased conspicuously and no serious adverse reactions occurred. We report for the first time four families with children with FD. The youngest child was only 1 year old. The four families included one girl which is rare in X-linked lysosomal storage diseases. Conclusion The clinical phenotype of FD in childhood is nonspecific, and the misdiagnosis rate is high. Most children with FD have a delayed diagnosis, and their organs are often seriously damaged in adulthood. Pediatricians must improve their diagnosis and treatment awareness, screen high-risk groups, and emphasize multidisciplinary cooperation and holistic lifestyle management after diagnosis. The diagnosis of the proband is also conducive to the mining of other cases of FD families and has important guiding significance for prenatal diagnosis.